Pelatihan Pembuatan Video Pembelajaran Pada Guru KB & TK Amal Insani Yogyakarta - Marfuah, Hasti Hasanati; Syah, Firdian; Wahana, Aditya (LPPM IST AKPRIND Yogyakarta, 2022)
Since the COVID-19 outbreak hits Indonesia in early March 2020, the government issued a policy that all students, from early childhood to university levels, conduct distance learning processes (from their homes). This is also done by the teachers in KB & TK Amal Insani. Distance learning is delivered by the teacher, one of which is by making simple learning videos made using cellphones. Based on the results of interviews with KB & TK Amal Insani leaders, distance learning carried out by teachers is evaluated every 2 months. A total of 77.2% stated that the learning videos made by the teacher helped children's learning activities at home. From the results of this evaluation, there are inputs from parents who want the learning videos to be made even more interesting so that they can increase children's enthusiasm for learning. The method of implementing this activity is by demonstration (providing examples and how to make learning videos) and mentoring. The target of this training activity is the teachers in KB & TK Amal Insani. The results obtained from this training activity are activity reports, training modules, and scientific articles.